2022
DOI: 10.48550/arxiv.2204.03423
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The last three years: multiband gravitational-wave observations of stellar-mass binary black holes

Abstract: Understanding the formation and evolution of the stellar-mass binary black holes discovered by LIGO and Virgo is a challenge that spans many areas of astrophysics, from stellar evolution, dynamics and accretion disks, to possible exotic early universe processes. Over the final years of their lives, stellar-mass binaries radiate gravitational waves that are first observable by spacebased detectors (such as LISA) and then ground-based instruments (such as LIGO, Virgo and the next generation observatories Cosmic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 71 publications
0
10
0
1
Order By: Relevance
“…This finding was later supported by more detailed followup work [98,99]. However, in an independent study [100], a more pessismistic prediction was provided. There it is found that for stellar-mass black systems, like GW150914, one can predict the arrival time in the LVK band with a precision of ∼ hours from observations in the LISA band.…”
Section: Arrival Timesmentioning
confidence: 79%
“…This finding was later supported by more detailed followup work [98,99]. However, in an independent study [100], a more pessismistic prediction was provided. There it is found that for stellar-mass black systems, like GW150914, one can predict the arrival time in the LVK band with a precision of ∼ hours from observations in the LISA band.…”
Section: Arrival Timesmentioning
confidence: 79%
“…These observatories can detect numerous bright GW sources, among which BNS, NS-BH and massive BBH. Moreover, a limited number of these sources might be observed in different frequency bands by both space and ground-based detectors, whose observations can then be combined to reduce uncertainties in the inference of the GW source parameters [92]. This combined analysis is expected to provide better determination of the luminosity distance measurement, though it might be applicable only to a small number of events [93][94][95].…”
Section: Gravitational Waves Observationmentioning
confidence: 99%
“…The primary signature here is not in the form of the signal itself, but instead even a small δ c GW will result in an 'arrival time' of the signal in the LVK band significantly different from what would be predicted from LISA observations of the signal itself. In [95] the authors find that for stellar-mass black systems, like GW150914, one can predict the arrival time in the LVK band with a precision of ∼ hours from observations in the LISA band. A δ c GW of ∼ 10 −13 for a source 100 Mpc away from the detectors will produce a arrival time delay of ∼ hours and is hence in principle detectable.…”
Section: B Arrival Timesmentioning
confidence: 99%
“…To increase the travel time by two minutes a value of only δ c GW = 3 × 10 −15 is required. To produce time shifts of ∼ 50000 seconds-roughly the accuracy at which an observation in the LISA band would be able to constrain the merger time [95]-would require 13 However, this time delay can quickly become very large. A value of only |δ c GW | = 8 × 10 −10 is required before the time delay is larger than a year and in such cases with a subluminal c GW we might observe the signal with LISA at the same time as the signal arriving at ground based observatories.…”
Section: Probing C Gw With Joint Lvk/lisa Observationsmentioning
confidence: 99%